PEMIKIRAN IBN KHALDUN MENGENAI SIFAT DAN AMALAN NEGATIF YANG BOLEH MERUNTUHKAN KEPIMPINAN ISLAM - Ab. Majid, Mohamad Kamil; Hamat, Mohd Fauzi (Journal of Al-Tamaddun, 2005)
lbn Khaldun is undoubtedly a prominent Islamic Thinker especially in the field of History and Islctmic Civilization. His Prolegomena (Muqaddimah) is considered the greatest work of its kind in the Philosophy rf History. This article tries to elaborate his thoughts on certain negative features and practices among Muslim leaders such as tyranny, dictatorship, extravagance, treachery, and seffishness. In our view, these need to be controlled and monilored in a proper manner and the foilure in doing so v,ill lead to the destruction of any civilization in this world.